Evaluation of three different bottom boards in honeybee hives for the control of Varroa destructor - Juri, Pablo; Nogueira, Enrique; Anzola, José; Rodríguez-Batista, Valentina; Branchiccela, Belén; Invernizzi, Ciro (Frontiers in Bee Science, 2024)
Varroa destructor stands as the primary global pest of honey bees, inflicting direct harm on bees while also acting as a vector for a multitude of viruses. Integrated pest management is widely recognized as the optimal strategy for minimizing acaricide application. Designed bottom boards that can limit the growth of the mite population by removing them from the hive preventing their return and reinfestation of the colony show promising potential. The aim of this study was to compare Varroa population growth by employing three different types of bottom boards. An apiary of 55 colonies was randomly divided into five groups according to the bottom board they had: 1) tubular bottom board, 2) screen bottom board, 3) sticky bottom board, 4) conventional bottom board with a permanent treatment with acaricide (positive control), and 5) conventional bottom board (negative control). Varroa infestation level in bees, colony strength (bee and brood population), and honey reserves were determined between April and December (between Autumn and Spring in Southern hemisphere). Colonies that had sticky bottom board had approximately 50% less Varroa infestation than colonies with conventional bottom board at the end of the study. Varroa infestation levels did not differ significantly between the tubular, screen and conventional bottom boards. Colony strength was similar in all groups. No differences were observed in honey production between colonies from different groups. The use of sticky bottom boards was the most promising board to limit Varroa population growth and prevent colonies' reinfestation.This result encourage future studies to analyze the incorporation of this strategy in integrated pest management programs.